2020
DOI: 10.1016/bs.aivir.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Viral cell-to-cell spread: Conventional and non-conventional ways

Abstract: A critical step in the life cycle of a virus is spread to a new target cell, which generally involves the release of new viral particles from the infected cell which can then initiate infection in the next target cell. While cell-free viral particles released into the extracellular environment are necessary for long distance spread, there are disadvantages to this mechanism. These include the presence of immune system components, the low success rate of infection by single particles, and the relative fragility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 204 publications
(346 reference statements)
2
35
0
Order By: Relevance
“…Although syncytium formation by herpesviruses has not gained much attention so far, all herpesviruses have been shown to be capable of forming syncytia during natural or in vitro infection [ 19 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Syncytium formation has been commonly reported for VSV, the most fusogenic herpesvirus, as well as for HSV and EBV, and several review articles covering these viruses have been published elsewhere [ 39 , 41 , 42 , 43 ]. During VZV infection, the presence of extensive syncytia in skin lesions as well as in the sensory ganglia is not only a hallmark of infection but also a diagnostic parameter [ 44 , 45 ].…”
Section: Syncytium Formation By Herpesvirusesmentioning
confidence: 99%
“…Although syncytium formation by herpesviruses has not gained much attention so far, all herpesviruses have been shown to be capable of forming syncytia during natural or in vitro infection [ 19 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Syncytium formation has been commonly reported for VSV, the most fusogenic herpesvirus, as well as for HSV and EBV, and several review articles covering these viruses have been published elsewhere [ 39 , 41 , 42 , 43 ]. During VZV infection, the presence of extensive syncytia in skin lesions as well as in the sensory ganglia is not only a hallmark of infection but also a diagnostic parameter [ 44 , 45 ].…”
Section: Syncytium Formation By Herpesvirusesmentioning
confidence: 99%
“…The involvement of TJs and AJs in cell-to-cell viral movement and their role as receptors have been reported for human viruses ( Cifuentes-Munoz et al, 2020 ), but there is no information on viruses using this route in arthropods. In humans, for instance, after primary infection of the respiratory airway, measles virus, family Paramyxoviridae , spreads laterally into the epithelium via AJs ( Mühlebach et al, 2011 ; Nakatsu et al, 2013 ).…”
Section: Cileviruses Movement Within Their Mite Vectors: a Critical E...mentioning
confidence: 99%
“…The various virus strains use varied protrusion-based strategies for intercellular spreading, including filopodial bridges, microtubule-negative or -positive TNTs, adherent junctions, etc. They can travel as packed virions, or as intact viruses bound to the membrane of the tubules and surf along it, bud from the filopodia membrane and in some cases they can use motor proteins, such as myosin 2A for transportation within the tube, as described in an excellent recent review (Cifuentes-Munoz et al 2020 ). Notably, respiratory viruses, such as RSV, human metapneumonia virus (HMPV) or the severe acute respiratory syndrome virus 2 (SARS-CoV-2), also use such filopodial extensions to spread (Cifuentes-Munoz et al 2020 ) the induction of which was found associated with increased casein kinase (CK2) signaling.…”
Section: Membrane Nanotubes As Intercellular Highways: Viruses and Bamentioning
confidence: 99%